2008
DOI: 10.1093/nar/gkn402
|View full text |Cite
|
Sign up to set email alerts
|

Effect of loop length variation on quadruplex-Watson Crick duplex competition

Abstract: The effect of loop length on quadruplex stability has been studied when the G-rich strand is present along with its complementary C-rich strand, thereby resulting in competition between quadruplex and duplex structures. Using model sequences with loop lengths varying from T to T5, we carried out extensive FRET to discover the influence of loop length on the quadruplex-Watson Crick duplex competition. The binding data show an increase in the binding affinity of quadruplexes towards their complementary strands u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 59 publications
5
61
1
Order By: Relevance
“…It is well established that the folding motif for any DNA intramolecular quadruplex is highly regulated by the types of loops present [15][16][17][18][19][20]. The types of loops present will determine: 1) the syn or anti conformations of the guanine bases; 2) the strand orientations (i.e., parallel, antiparallel or mixed parallel-antiparallel); and 3) the orientation of the hydrogen bonds within one G-tetrad relative to the G-tetrad above and below [21].…”
Section: Duplexmentioning
confidence: 99%
“…It is well established that the folding motif for any DNA intramolecular quadruplex is highly regulated by the types of loops present [15][16][17][18][19][20]. The types of loops present will determine: 1) the syn or anti conformations of the guanine bases; 2) the strand orientations (i.e., parallel, antiparallel or mixed parallel-antiparallel); and 3) the orientation of the hydrogen bonds within one G-tetrad relative to the G-tetrad above and below [21].…”
Section: Duplexmentioning
confidence: 99%
“…Recent studies have shown that human telomeres form GQ structures in vivo (12,13) and in cell extracts (14). At physiologically relevant ionic conditions (∼150 mM K + ), GQs are thermodynamically more stable than competing Watson-Crick pairing (15). These structures were often regarded as obstacles for recruitment of telomerase (16) and translocation of the DNA replication machinery (17), and their unfolding requires helicase activity (17)(18)(19) or ssDNA binding proteins (20,21).…”
mentioning
confidence: 99%
“…These studies combined make telomere sequences prime subjects for direct-effect IR damage which is why in future experiments we would like to generate DNA substrates that simulate in vivo telomeric DNA. These would include double-stranded telomeric DNA and the highly stable G-quadruplex structures within the single-stranded G-rich overhang (Biffi et al 2013; Gomez et al 2006; Hänsel et al 2013; Kumar et al 2008; Lam et al 2013; Sen et al 1988; Wu et al 2008; Paeschke 2005; Paeschke et al 2008). …”
Section: Discussionmentioning
confidence: 99%